Splicing modulators elicit global translational repression by condensate-prone proteins translated from introns. Issue 2 (17th February 2022) - Chhipi-Shrestha, Jagat K.; Schneider-Poetsch, Tilman; Suzuki, Takehiro; Mito, Mari; Khan, Khalid; Dohmae, Naoshi; Iwasaki, Shintaro; Yoshida, Minoru
Summary: Chemical splicing modulators that bind to the spliceosome have provided an attractive avenue for cancer treatment. Splicing modulators induce accumulation and subsequent translation of a subset of intron-retained mRNAs. However, the biological effect of proteins containing translated intron sequences remains unclear. Here, we identify a number of truncated proteins generated upon treatment with the splicing modulator spliceostatin A (SSA) via genome-wide ribosome profiling and bio-orthogonal noncanonical amino acid tagging (BONCAT) mass spectrometry. A subset of these truncated proteins has intrinsically disordered regions, forms insoluble cellular condensates, and triggers the proteotoxic stress response through c-Jun N-terminal kinase (JNK) phosphorylation, thereby inhibiting the mTORC1 pathway. In turn, this reduces global translation. These findings indicate that creating an overburden of condensate-prone proteins derived from introns represses translation and prevents further production of harmful truncated proteins. This mechanism appears to contribute to the antiproliferative and proapoptotic activity of splicing modulators. Graphical abstract: Highlights: Retained introns induced by spliceostatin A generate an array of truncated proteins The truncated proteins are intrinsically disordered and form cellular condensates SSA-induced proteotoxicity activates JNK and inhibits mTORC1 pathways SSA ultimately attenuates global protein synthesis Abstract : Chhipi-Shrestha et al. show that splicing modulation leads to widespread translation from retained introns, supplying intrinsically disordered proteins to form insoluble condensates and to induce cellular proteotoxicity. Activated JNK inhibits the mTORC1 pathway and ultimately reduces the global translation, suppressing the further generation of harmful truncated proteins.